Can δίκαιον be ὅσιον? A Note on Scholl. Plat. Resp. I 344A8 and Leg. IX 857B5 - Cufalo, Domenico (Literatūra, 2016)
In this paper I will focus on a crux in two Platonic scholia, where manuscripts have the impossible διονύσιον, but Greene suggests δίκαιον. This amendment was made on the basis of a gloss of Photius’ Lexicon, although the corresponding gloss of Suidas confirms the text of Platonic scholia. However the agreement with Photius is not so important, not only because it is impossible to prove that he reproduces the text of the glossary composed by the Atticist Aelius Dionysius without any modification (it is also the source of Suidas and other Byzantine lexica, and especially of the so called Erweiterte Synagoge, which the Platonic scholia derive from as well), but also because our scholia reveal elsewhere a major affinity with Suidas than with Patriarch’s Lexicon. In the light of a careful review of the loci paralleli I therefore suggest the reading δημόσιον.